2017
DOI: 10.1093/icvts/ivx067
|View full text |Cite
|
Sign up to set email alerts
|

Transapical transcatheter mitral valve-in-valve implantation versus minimally invasive surgery for failed mitral bioprostheses†

Abstract: In selected patients, M-VIV can be performed safely with results comparable with those of surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Of 270 potentially relevant articles screened initially, 17 eligible studies including a total of 1017 patients undergoing VIV/VIR‐TMVI were identified (Table ). Only two small‐size study compared VIV‐TMVI with redo MVS, and one of them using a propensity‐score analysis .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 270 potentially relevant articles screened initially, 17 eligible studies including a total of 1017 patients undergoing VIV/VIR‐TMVI were identified (Table ). Only two small‐size study compared VIV‐TMVI with redo MVS, and one of them using a propensity‐score analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Of 270 potentially relevant articles screened initially, 17 eligible studies including a total of 1017 patients undergoing VIV/VIR‐TMVI were identified (Table ). Only two small‐size study compared VIV‐TMVI with redo MVS, and one of them using a propensity‐score analysis . Eleven studies analyzed exclusive VIV‐TMVI patients, only one study examined exclusive VIR‐TMVI patients, two studies investigated combined VIV/VIR‐TMVI patients, and three studies researched VIV‐TMVI and VIR‐TMVI patients separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations